ANALISIS PERHITUNGAN ASET DAN LIABILITAS BERDASARKAN PENILAIAN STANDAR AKUNTANSI KEUANGAN (SAK) DAN PRAKTEK AKUNTANSI ASURANSI (STATUTORY ACCOUNTING PRACTICES) PADA PT. ASURANSI JIWA MEGA LIFE - Siti Nurlatifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This research aims to (1) determine the amount of the difference between GAAP (Generally Accepted Accounting Principles) and SAP (Standar Accounting Practices) assessment and the amount of assets that are not allowed in the calculation of assets, (2) determine the amount of the difference between GAAP and SAP ratings in the calculation of liabilities PT Asuransi Jiwa Mega Life period in 2016 and (3) determine the value Risk Based Capital (RBC) associated with the achievement of the solvency ratio of PT Asuransi Jiwa Mega Life period in 2016. The conclusion that can be drawn from this research is the analysis of the calculation of assets under GAAP and SAP assessment there are some assets that suffered the difference, with a total difference of Rp. 121,101.23 million; in the analysis of liability calculation based on GAAP and SAP ratings are experiencing excess liability, ie at a premium of reserves Rp. 44.145 million; in the analysis of the value of the Risk-Based Capital (RBC) adequacy relating to the calculation of the solvency ratio of achievement, the research found that (1) the largest amount of funds needed to anticipate the risk of loss that may arise as a result of the deviation in the management of assets and liabilities is at Risk Liability Insurance (Schedule D) that is equal to 49.90% (Rp. 26,445.87 million) of the total number of RBC Rp. 52,996.63 million (2) the achievement of the solvency ratio achieved by the Life Insurance Company Megalife period of 2016 by 670%, meaning that if all customers to make a claim, the insurance company can meet all of its liabilities and still have a reserve of 570%.